Digitizing Sports Arenas: New Trends and Technologies - Malak Jibraili (International Journal of Scientific Research and Innovative Studies, 2024)
The digital revolution has transformed the world we live in, including the professional realm, which has harnessed its advantages. Digital technologies are widespread in the sports world, used daily in all its facets: strategically employed by brands, leveraged by coaches and athletes to optimize performance. It's worth noting that the sports spectacle accompanies and even inspires technical innovations (Wille, 2015)1, and the adoption of these tools provides a decisive "competitive advantage," both in sports and commercially (Giblin et al., 2016)2. For the field of sports marketing, the rise of digital offers fervent and loyal supporters, the famous fans, a new way to experience current sports events and immerse themselves in them (Bailey, 2017)3. Today, we talk about a "connected match," a "smart stadium," and "digital sports." It is essential to understand how the introduction of technological tools within sports facilities, especially in the behavior of fans, positively or negatively changes the landscape. A literature review outlines the technological tools introduced in sports venues, the role of social media as a new communication channel, and the digital's position in the sports entertainment industry. A qualitative study then confronts the views of sports managers with those of fans regarding the role of various technological tools within sports facilities. Key words: Sports Venue, Sports Industry, Technologies, Digital Received Date: April 13, 2024 Accepted Date: May 15, 2024 Published Date: June 01, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/157 DOI: https://doi.org/10.5281/zenodo.11245185